Conceptions of distance education and financial mathematics from an onto-historical understanding (2019)
Mathematics as a system of knowledge organized in distance education, in continuous expansion is applied in almost all disciplines of knowledge, is aimed at stimulating the development of cognitive skills, as well as analytical and critical skills, whose importance lies in the theory of value, seeks to discover manifestations to the development of the capacity for self-determination, collective autonomy and solidarity. The research was developed under the mixed paradigm, supported by a historical-dialectical and quantitative approach of confirmatory factor analysis, having as key informant's managers, tutors, graduates and students of different programs of distance education. His ontology from the nature of the reality, was to generate a theoretical and didactic approach from the onto - historical understanding of financial mathematics in the trajectory of programs in distance education. The results obtained show that there is a significant relationship between the modality, the critical dialogical approach in the teaching of financial mathematics and technology. It is concluded that the conception of distance education is determined as an opportunity to be professional, for low-income youth who live in vulnerable areas, and have labour commitments. The structural model identifies factors, motivation, human relationships and resources, associated with the conception and development of cognitive skills in financial mathematics